2022
DOI: 10.21741/9781644902059-42
|View full text |Cite
|
Sign up to set email alerts
|

Usage of Unmanned Aerial Vehicles in Medical Services: A Review

Abstract: The usage of drone technology has increased in a vast range of disciplines, including medical services. Drones can aerially deliver medical supplies and laboratory test samples during health emergencies such as the COVID-19 pandemic. It can also be used as a delivery device for an automated external defibrillator which might significantly increase the survival chances of out-of-hospital cardiac arrest victims. Significant cost savings compared with ground transportation and speed of delivery will probably driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…BVLOS operations offer new means of delivering value-added services via a wide range of applications, ranging from remote sensing for object detection and tracking [6]; search and rescue operations; disaster and crisis management [7]; precision agriculture [8]; or environmental monitoring [9] to logistics and industrial applications such as freight transportation [10] or the delivery of medical supplies [11]. This 'plateau of productivity' holds particular promise but demands new technical and regulatory capabilities to support drone operations in long range as well as UAS operation in the future high volumes of air traffic.…”
Section: Opportunities and Challengesmentioning
confidence: 99%
“…BVLOS operations offer new means of delivering value-added services via a wide range of applications, ranging from remote sensing for object detection and tracking [6]; search and rescue operations; disaster and crisis management [7]; precision agriculture [8]; or environmental monitoring [9] to logistics and industrial applications such as freight transportation [10] or the delivery of medical supplies [11]. This 'plateau of productivity' holds particular promise but demands new technical and regulatory capabilities to support drone operations in long range as well as UAS operation in the future high volumes of air traffic.…”
Section: Opportunities and Challengesmentioning
confidence: 99%
“…Unmanned aircraft systems (UAS) or drones, have the unique ability to overcome the obstacle of geographic location with significant reduction in cold ischemic times [61]. In the current era, drone-delivery in the medical community has been used for delivery of biological samples, blood products, search and rescue, as well as automated external defibrillators (AED) [62,63]. In 2021, Scalea et al, reported the first successful delivery of a human kidney that was ultimately transplanted into a recipient [64].…”
Section: Unmanned Aircraft Systems (Uas)mentioning
confidence: 99%